The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1186/1751-0147-54-55
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific ketoprofen concentrations in plasma after oral and intramuscular administration in growing pigs

Abstract: BackgroundKetoprofen is a non-steroidal anti-inflammatory drug which has been widely used for domestic animals. Orally administered racemic ketoprofen has been reported to be absorbed well in pigs, and bioavailability was almost complete. The objectives of this study were to analyze R- and S-ketoprofen concentrations in plasma after oral (PO) and intra muscular (IM) routes of administration, and to assess the relative bioavailability of racemic ketoprofen for both enantiomers between those routes of administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…However, the R(+)-ketoprofen enantiomer may be a more potent analgesic according to a study assessing mechanical nociceptive threshold (21). In many species, S(-)-ketoprofen predominates over R(+)-ketoprofen in terms of plasma exposure following intramuscular administration of racemic ketoprofen (22,(37)(38)(39). The current study also found this to be true in piglets, and additionally found that this was also true for interstitial fluid exposure.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, the R(+)-ketoprofen enantiomer may be a more potent analgesic according to a study assessing mechanical nociceptive threshold (21). In many species, S(-)-ketoprofen predominates over R(+)-ketoprofen in terms of plasma exposure following intramuscular administration of racemic ketoprofen (22,(37)(38)(39). The current study also found this to be true in piglets, and additionally found that this was also true for interstitial fluid exposure.…”
Section: Discussionsupporting
confidence: 63%
“…It is additionally important to consider the stereoselective pharmacokinetics of ketoprofen, rather than simply total ketoprofen concentration, as plasma concentration and pharmacodynamic effect of each enantiomer differs between species (37). Previous studies in pigs have reported that the S(-)-enantiomer is a more potent cyclooxygenase-inhibitor, and therefore displays greater anti-inflammatory effects compared to the R(+)-enantiomer (22,38).…”
Section: Discussionmentioning
confidence: 99%
“…31 Maximum concentrations were 7.42 mg/L for S-ketoprofen and 2.55 mg/L for R-ketoprofen when administered orally in pigs. 32 The concentration of ketoprofen in plasma was 4.5-8.4 μg/mL in our sheep at 2 h after administration and R-ketoprofen has been recorded as the most prominent enantiomer found in sheep. 17 Based on these results, oral administration of the three NSAIDs at twice the standard parental dose shown to be therapeutic in other species was expected to be still within the therapeutic range for sheep; however, it is recommended that work should be done to identify the therapeutic levels in sheep.…”
Section: Discussionmentioning
confidence: 96%
“…The intravenous (i.v.) or extravascular administration of racemic KTP demonstrated enantioselective PK in sheep, camels, pigs, horses, dogs, cats and poultry, with a predominance of the S(+) enantiomer in plasma of most species, except for sheep, camels and poultry, in which R(−) KTP predominated (Delatour et al ., ; Jaussaud et al ., ; Landoni & Lees, ; Landoni et al ., ; Al Katheeri et al ., ; Arifah et al ., ; Lees et al ., ; Fosse et al ., ; Neirinckx et al ., ; Mustonen et al ., ). In contrast, the i.v.…”
Section: Pharmacokinetic Parameters (Mean ± Sd) Of R(−) and S(+) Ktp mentioning
confidence: 97%